PEMBUATAN TRAINER KIT MICROCONTROLLER ATMega8 - , ROBI ISWADI, I. Aris Hendaryanto, ST., M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nowadays, microcontroller is a popular hardware in the industrial revolution which is used as a primary controller, therefore this study entitled âThe Planning and Making Trainer Kit Microcontroller ATMega8â. The purposes of the study are making the trainer kit to be used for the electronical laboratory at the Machine Diploma Programme, to make the students understand about the system of controll ATMega8, and to make the students learn more about the components of microcontroler which have many benefits for the industrial world. The methodology of this study is literature data collecting from the library and internet, tool planning which use acrylic as simulating and result data collecting information, and tools testing which have many steps, there are information collecting, the schematic tools planning, and report writing. The results of this study shows that the trainer kit and control system are useful and simple to be applied. The control and electric system are never learnt directly. It also can be presented with training kit.